An Analysis on factors affecting organic farm management of LG members, Kudumbashree in Thrissur District - et. al., Brighty Jose, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organic farming is nothing but farming of crops without including any toxic elements which is harmful to the human being as well as to the soil. The central Government and state Government are introducing so many projects and plans to encourage and motivate organic farming. Kudumbashree is a women network of Kerala which stands for empowering the rural women. This network has started recently the concept of organic farming among its members which help the famers to cultivate the crops organically. This study aims to analyse the various factors which affect the organic farming of these members in Thrissur district. The factors identified for the research are opportunities for promotion, factors of certification, attitude and perception of farmers and society, manure and treating farm waste.